2020
DOI: 10.1242/jeb.218271
|View full text |Cite
|
Sign up to set email alerts
|

The role of the gut microbiome in mediating standard metabolic rate after dietary shifts in the viviparous cockroach,Diploptera punctata

Abstract: Diet may be a significant determinant of insect gut microbiome composition. However, the extent to which dietary shifts shape both the composition and relevant functions of insect gut microbiomes, and ultimately impact host energy balance (i.e. metabolic phenotype), is not well understood. We investigated the impacts of diet switching on Diploptera punctata females maintained on a dog food (DF) diet relative to those fed a comparatively sub-optimal cellulose-amended dog food (CADF) diet for 4 weeks. After this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(33 citation statements)
references
References 91 publications
0
17
2
Order By: Relevance
“…However, physiological adaptations to imbalanced diets, such as increasing gut length, may be metabolically costly (Yang and Joern, 1994). The few studies that have examined the impact of manipulating the nutritional composition of diets have generally found that nutritionally poor diets elevate average RMR (Zanotto et al, 1997;Ayayee et al, 2018Ayayee et al, , 2020; but see Clark et al, 2016). Typically, these studies considered short-term impacts of diet on metabolism during either adulthood or a single juvenile stage, ignoring the impact of the nutritional composition of diets on the scaling of RMR with body mass or size.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, physiological adaptations to imbalanced diets, such as increasing gut length, may be metabolically costly (Yang and Joern, 1994). The few studies that have examined the impact of manipulating the nutritional composition of diets have generally found that nutritionally poor diets elevate average RMR (Zanotto et al, 1997;Ayayee et al, 2018Ayayee et al, , 2020; but see Clark et al, 2016). Typically, these studies considered short-term impacts of diet on metabolism during either adulthood or a single juvenile stage, ignoring the impact of the nutritional composition of diets on the scaling of RMR with body mass or size.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study found that adult stick insects exhibit developmental diet-dependent differences in RMR when reared from birth on leaves from plant species varying in their nutritional content and digestibility (Hill et al, 2020), but the impact of developmental diet on the scaling of RMR and body mass was not considered. Shorter term studies conducted in adult insects only are more common, and have typically observed a reduction in RMR in response to a nutritionally poor diet (Zanotto et al, 1997;Ayayee et al, 2018Ayayee et al, , 2020; but see Clark et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, members of the bacterial order Pseudomonadales (Pseudomonadaceae and Moraxellaceae; class Gammaproteobacteria) were also abundant in eggs and adults and to a lesser extent in larvae. Several bacterial orders and families under the class gammaproteobacteria are recognized members of the gut microbiome across several insect species, serving as providers of metabolic nitrogen [3,46,47], essential amino acids [4,44], and microbe-derived hydrolytic enzymes [45,46]. These representative taxa may be performing similar functions in S. albicosta.…”
Section: Discussionmentioning
confidence: 99%
“…The past two decades have seen a tremendous increase in the availability of data detailing the microbial compositions of the gut microbiomes of various insects and the postulated functions of these gut microbiomes [1,2]. In some particular instances, the functions of insect gut microbiomes have been demonstrated to include nitrogen provisioning [3], essential amino acid provisioning [4][5][6][7], and an overall propensity for essential nutrient provisioning followed by detoxification and digestion [8]. These functions have been uncovered in both insect species considered pests and non-pests.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study found that adult stick insects exhibit developmental diet dependent differences in RMR when reared from birth on leaves from plant species varying in their nutritional content and digestibility (Hill, Silcocks and Andrew, 2020), but the impact of developmental diet on the scaling of RMR and body mass was not considered. Shorter term studies conducted in adult insects only are more common, and have typically observed a reduction in RMR in response to a lower quality diet (Zanotto et al ., 1997; Ayayee et al ., 2018, 2020, but see Clark, Zera and Behmer, 2016).…”
Section: Introductionmentioning
confidence: 99%